ANALISA SISTEM POSITIONING OBJEK PADA AREA INDOOR BERBASIS BLE DAN RASPBERRY PI - Afifah Dwi Ramadhani; Achmad Ilham Imanuddin; Kholidiyah Masykuroh (Jurnal RESISTOR (Rekayasa Sistem Komputer), 2022)
BLE technology can assist in indoor positioning system (IPS) applications. The IPS has an important role in determining the position of objects that are useful for monitoring or tracking. One of the methods is trilateration by utilizing the RSSI value between the transmitter and receiver to calculate the distance. In addition, we can use indoor paths loss modeling to calculate the distance. However, the RSSI method still has weaknesses due to fluctuations in measurement values caused by the effect of multipath and attenuation on the signal. So that there will be an error while we estimate the position and causes the accuracy to be weak. Besides the fluctuation of RSSI, the accuracy is also influenced by the geometric position between the transmitter and receiver. Geometric Dilution of Precision is a method that calculates the geometric value. In this study, we applied object positioning techniques using the BLE devices and the trilateration method. We analyzed the position accuracy by considering the mean of RSSI, the median of RSSI, and GDOP. The results show that taking into account the GDOP, the accuracy increases by 53% compared to the average RSSI scenario. And the accuracy value also increased 63% compared to the median RSSI scenario.